Effect on the growth and development and induction of abnormalities by a glyphosate commercial formulation and its active ingredient during two developmental stages of the South-American Creole frog, Leptodactylus latrans - Bach, Nadia Carla (2016)
We evaluated the acute lethal and sublethal effects of technical-grade glyphosate (GLY) and the GLY-based commercial formulation Roundup ULTRA MAX® (RU) on two Gosner stages (Gss) 25 and 36 of the South-American Creole frog, Leptodactylus latrans. Bioassays were performed following standardized methods within a wide range of concentrations (0.0007–9.62 mg of acid equivalents per liter—a.e./L—of RU and 3–300 mg/L of GLY). The endpoints evaluated were mortality, swimming activity, growth, development, and the presence of morphologic abnormalities, especially in the mouthparts. No lethal effects were observed on larvae exposed to GLY during either Gs-25 or Gs-36. The concentrations inducing 50 % lethality in RU-exposed larvae at different exposure times and Gss ranged from 3.26 to 9.61 mg a.e./L. Swimming activity was affected by only RU. Effects on growth and development and the induction of morphologic abnormalities—like oral abnormalities and edema—were observed after exposure to either GLY or RU. Gs-25 was the most sensitive stage to both forms of the herbicide. The commercial formulation was much more toxic than the active ingredient on all the endpoints assessed. Effects on growth, development, and the induction of morphologic abnormalities observed in the range of environmental concentrations reported for agroecosystems of Argentina constitute an alert to the potential detrimental effects of the herbicide that could be affecting the fitness and survival of anurans in agroecosystems.